THE EQUALITY COURT’S VIEW ON AFFIRMATIVE ACTION AND UNFAIR DISCRIMINATION Du Preez v The Minister of Justice and Constitutional Development 2006 5 SA 592 (EqC) - Adriaan van der Walt; Peter Kituri (Obiter, 2022)
So pervasive are the consequences of our segregated past that the need for reform to redress the resultant imbalances cannot be doubted. Affirmative action is the catalyst. There are inherent difficulties in applying affirmative action measures. These include, firstly, the means to ensure the objective and effective application of affirmative action, and secondly, the extent to which previously advantaged groups are to be excluded. The present case illustrates the difficulties that courts are faced with in a challenge by amember of a previously advantaged group against alleged unfair discrimination due to the implementation of affirmative action measures. It is the first reasoned judgment of the High Court sitting as an Equality Court in this regard and, for this reason, is of particular significance.